A flexible scintillation light apparatus for rare events searches. Issue 6 (May 2016) - Gironi, L; Baldazzi, G; Bonvicini, V; Campana, R; Capelli, S; Evangelista, Y; Fasoli, M; Feroci, M; Fuschino, F; Labanti, C; Marisaldi, M; Previtali, E; et al.
Abstract: FLARES (a Flexible scintillation Light Apparatus for Rare Event Searches) is a project for an innovative detector technology to be applied to rare event searches, and in particular to neutrinoless double beta decay experiments. Its novelty is the enhancement and optimization of the collection of the scintillation light emitted by ultra-pure crystals through the use of arrays of high performance silicon photodetectors cooled to 120 K. This would provide scintillation detectors with ~1% level energy resolution, with the advantages of a technology offering relatively simple low cost mass scalability and powerful background reduction handles, as requested by future neutrinoless double beta decay experimental programs.